Losing Our Humanity: The Self-Dehumanizing Consequences of Social Ostracism. (February 2013) - Bastian, Brock; Jetten, Jolanda; Chen, Hannah; Radke, Helena R. M.; Harding, Jessica F.; Fasoli, Fabio
People not only dehumanize others, they also dehumanize the self in response to their own harmful behavior. We examine this self-dehumanization effect across four studies. Studies 1 and 2 show that when participants are perpetrators of social ostracism, they view themselves as less human compared with when they engage in nonaversive interpersonal interactions. Perceived immorality of their behavior mediated this effect. Studies 3 and 4 highlight the behavioral consequences of self-dehumanization. The extent to which participants saw themselves as less human after perpetrating social ostracism predicted subsequent prosocial behavior. Studies 2 to 4 also demonstrate that consequences of self-dehumanization occur independently of any effects of self-esteem or mood. The findings are discussed in relation to previous work on dehumanization and self-perception. We conclude that in the context of immoral actions (self) dehumanization may be functional.